Authentic Leadership, Trust (in the Leader), and Flourishing: Does Precariousness Matter? - Kleynhans, Deon J.; Heyns, Marita M.; Stander, Marius W.; de Beer, Leon T. (Frontiers in Psychology, 2022)
Abstract Orientation: This study employed a second stage moderated mediation analysis to investigate the influence of authentic leadership on employee flourishing via trust in the leader (mediating variable) and job overload (moderating variable). Research purpose: To explore the relationship between authentic leadership and flourishing by considering the indirect effect of trust in the leader as potentially moderated by job overload. Motivation for the study: An authentic leadership style, trust in the leader, and job overload may impact employee flourishing. A deeper understanding of the potential interaction effect of trust in the leader and job overload in the relationship between authentic leadership and flourishing may improve individual and organizational productivity. Research approach/design and method: This study used a quantitative, cross-sectional survey design and PROCESS for moderated mediation. The sample consisted of 314 employees in a prominent steel manufacturing organization in South Africa. The Authentic Leadership Inventory, Workplace Trust Survey, Flourishing-at-Work Scale, and the Job Demands Resources Scale were utilized. Main findings: The study found that authentic leadership was a significant predictor of flourishing through trust in the leader. Job overload did not moderate the relationship between trust in the leader and employee flourishing. Practical/managerial implications: This study emphasizes the potential role of authentic leadership in fostering a trustful relationship between employees and their leaders. It might result in the increased flourishing of employees. The non-significant influence of job overload on trusting relationships in precarious work contexts was also illuminated. Contribution/value-add: Through the analysis of these relations, organizations may be favorably equipped to optimize the resources required to improve performance. Moreover, the investigation into trust in the leader combined with job overload increases our understanding of supporting and promoting employee flourishing at work.